WHY GOVERNMENT AND LOCAL POPULATIONS SUPPORT MEGA SPORTING EVENTS: A CASE OF THE FIFA 2022 WORLD CUP IN QATAR - Khalifa, Nasser AL-Dosari (Journal of Public Policy and Administration, 2020)
Purpose: This research aimed at finding out the various reasons that encourage governments and their citizens to support the hosting of mega sporting events. Methodology: The research employed a quantitative design through the use of questionnaire that incorporated a case study on the government and the local population of Qatar in the context of the 2022 FIFA World Cup in Qatar. This design was further enhanced by the use of the causal effect of social exchange theory to analyse the aims of the research. The study relied on a sample size of 61 respondents out of the 100 target population who were randomly sampled. The quantitative data collected was analysed using the SPSS version 25 for data analysis through the use of descriptive statistics. Further data analysis was conducted using factor analysis and structural equation modelling. A Cronbach's reliability test of internal consistency of the questionnaire used was conducted followed by the estimation of the descriptive statistics as well as the variance inflation factor (VIF) tests for collinearity backed with a Pearson's correlation test. Findings: The impact perceptions were found to influence positive support for mega sports events with variations in income levels and life quality. Unique contribution to theory, practice and policy: The study recommended further studies to be conducted on the individual factors that form the impact perceptions of mega sports events. The study provides policy makers with empirical evidence that may be relied on in policy making to ensure positive influence on impact perceptions that encourage governments and local populations to support hosting mega sporting events. Further, the recommendation of the study provides a research gap and empirical evidence that future researchers can rely on in studying the individual factors that form the impact perceptions of mega sports events.